Transformative Islamic Education: Concepts, Foundations, and Objectives - Nur Aziza; Zuhdiyah Zuhdiyah; Asri Karolina (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2025)
Transformative Islamic education represents an educational paradigm that integrates Islamic values with social realities to develop individuals who are spiritually, intellectually, and morally holistic. This study aims to elucidate the foundational concepts and objectives of transformative Islamic education, as well as its significance within the Indonesian educational context. Employing a qualitative library research methodology, relevant literatures on Islamic education and social transformation were analyzed. Findings indicate that this educational approach transcends mere knowledge transmission, focusing instead on character development, humanistic values, and the cultivation of critical and participatory thinking. Rooted in core Islamic principles such as tauhid (the oneness of God) and human stewardship as khalifah (vicegerents), its objectives include enhancing individual quality, fostering social awareness, promoting justice, and integrating knowledge with spirituality. Consequently, transformative Islamic education plays a strategic role in nurturing generations capable of confronting contemporary challenges and contributing meaningfully to a just and civilized society.